Dynamic simulation of a circulating fluidized bed boiler system Part II: Simulation of a boiler system operating in a power plant - Kim, Seongil; Choi, Sangmin; Yang, Jongin (Journal of mechanical science and technology, 2016)
A case of dynamic performance simulation model of a CFB boiler is presented in this study. The dynamic system of a CFB boiler in an operating power plant and the transient behavior of sub-models is described in the accompanying paper, Part I. The current paper, Part II, describes the model extension for the CFB boiler system in a power plant. The open loop model in Paper I was expanded by applying a set of PID (Proportional-integral-differential) control loops. In the control loop, pressure, temperature, mass flow rate of the main steam, the drum water level and the oxygen level at the stack were controlled. Dynamic performance was simulated to check the response of the closed control loop. Finally, performance of the total boiler system for a range of operation load of the power plant was simulated, where the parameters were calculated and control variables were maintained at the set values by PID control. Dynamic performance of a boiler at a selected load variation case was simulated and compared with actual measurements and their transient response characteristics were discussed. The simulation can also directly produce useful operation parameters, which are not measurable, but could be used for engineering evaluation.